Nodal Pricing: The Theory and Evidence of Indonesia Power System - Hakam, Dzikri Firmansyah (International Journal of Energy Economics and Policy, 2018)
This research presents a stylised nodal pricing model of Indonesia power system with engineering-economic constraints. The modelling in this research adopts the 8 nodes stylised model for the Sumatra power system, by incorporating generation, transmission and power system stability constraint. Nodal pricing analysis is performed based on Direct Current (DC) Optimal Power Flow (OPF) and marginal cost calculation in each node. This research is the first ever to estimate nodal prices in the Indonesian electricity market. Nodal pricing model in this paper provides a proper investment signals for Indonesian stakeholder in performing generation expansion planning. Keywords: nodal pricing, Sumatra power system, stylised model JEL Classifications: C610, D410, D470, D600 DOI: https://doi.org/10.32479/ijeep.6747